A capillary electrophoresis method for identifying forensically relevant body fluids using miRNAs. (January 2018) - Mayes, Carrie; Seashols-Williams, Sarah; Hughes-Stamm, Sheree
Highlights: A co-extraction method was used to perform STR analysis and miRNA body fluid identification from the same sample. The miRNA system is compatible with techniques and instrumentation currently used in crime labs. Samples of venous blood, menstrual blood, semen, and saliva were able to be differentiated. Abstract: Body fluid identification (BFID) can provide crucial information during the course of an investigation. In recent years, microRNAs (miRNAs) have shown considerable body fluid specificity, are able to be co-extracted with DNA, and their small size (18–25 nucleotides) make them ideal for analyzing highly degraded forensic samples. In this study, we designed a preliminary 8-marker system for BFID including an endogenous reference gene (let-7g) to differentiate between venous blood (miR-451a and miR-142-3p), menstrual blood (miR-141-3p and miR-412-3p), semen (miR-891a and miR-10b), and saliva (miR-205) using a capillary electrophoresis approach. This panel uses a linear primer system in order to incorporate additional miRNA markers by forming a multiplex system. The miRNA system was able to distinguish between venous blood, menstrual blood, semen, and saliva using a rudimentary data interpretation strategy. All STR amplifications from co-extracted DNA yielded complete profiles from human identification purposes.